Análisis jurídico de la eficacia y aplicación de las medidas de amparo establecidas en la Ley Contra La Violencia A La Mujer Y La Familia Ecuatoriana - Villarreal León, José Patricio (2015)
The family is the fundamental and principal nucleus of society and necessary for proteccion rights and the integral development of all its members; for this reason, the family musterceive the support and protection of the Ecuadorian state, so that each of its members to fully exercise the ir rights and fulfill the ir obligations. Domestic violence is one of the evil sthatafflictour society, does not distinguish social class, or gender. It is the state, preventing any kind of violence, in order to enrich family relationships. The effective enessof the protection measures, lies in a correctimplementation of the Lawon Violence Against Women and Family. The law Against Violence to Women and Families, recognizes no jurisdiction to bee minentlyguarantarof human rights of the victim. Being the family, the basic unit of society the act provides for protection measures in order to protect all its members. Victim domestic violence is considered anyone’s spouse abuser or has cohabited with him somehow